Correction of the nucleotide sequence of the Citrobacter freundii tryptophan operon regulatory region. - Kuroda, M I (1984)
We present a correction of the previously reported nucleotide sequence of the Citrobacter freundii trp operon regulatory region. The original sequence analyses were performed with a plasmid designated pCF2. We repeated the cloning of the trp regulatory region of C. freundii and concluded from the determined sequence that a DNA rearrangement had occurred within the leader region of the cloned trp DNA of pCF2. The correct sequence is homologous to the Escherichia coli sequence.